KEY CONCEPTS OF INSTANTIAL USE IN DISCOURSE (Journal of Science-Innovative Research in Uzbekistan, 2023)
The concept of stability is a cornerstone of phraseological theory.  Another key aspect of stylistic use is the involvement of phraseology in semantic  and stylistic cohesion of discourse and the stability of these interrelationships as a  manifestation of the inherent cohesion of the base form. The theory of stylistic  pattern is also one of the fundamental concepts in instantial stylistic use. Pattern is a  basic structural element, carrying semantic and stylistic information and serving as  a framework for discoursal change and sustainability of phraseological image over longer stretches of text.